2003
DOI: 10.1161/01.cir.0000065606.63163.b9
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Normalizes Autonomic Neural Control in Experimental Heart Failure

Abstract: Background-HMG-CoA reductase inhibitors (statins) have been shown to beneficially affect outcomes in chronic heart failure (CHF). We hypothesized that statins exert effects on autonomic function, as assessed by plasma norepinephrine levels, direct recordings of renal sympathetic nerve activity (RSNA), and baroreflex function. Methods and Results-Normolipidemic CHF rabbits were treated with simvastatin or vehicle. CHF was induced by continuous ventricular pacing at 320 to 340 bpm for 3 weeks. Two to 3 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 60 publications
7
121
0
4
Order By: Relevance
“…A modulating effect of statin therapy has been also reported on the sympatho-vagal balance in patients with ichaemic heart disease [25,26]. Accordingly, a modulatory effect on vagal tone should have been influencing the VO 2 gas kinetics by improving exercise chronotropic responsiveness.…”
Section: Discussionmentioning
confidence: 96%
“…A modulating effect of statin therapy has been also reported on the sympatho-vagal balance in patients with ichaemic heart disease [25,26]. Accordingly, a modulatory effect on vagal tone should have been influencing the VO 2 gas kinetics by improving exercise chronotropic responsiveness.…”
Section: Discussionmentioning
confidence: 96%
“…We believe the large difference in survival for patients treated with statin therapy or not (97 vs. 84% at 1-year follow-up) may be due to the many actions of statins. Potential mechanisms include reduced inflammation, 10,11 reduced ischemia, 17,18 improved LV function, 14,15 and/or other pleiotropic effects, 19,20 all effects of statin therapy that reduce the likelihood of mortality in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…109 As with ACEIs and aldosterone antagonists, statins also improve mortality in cardiomyopathy patients. Pliquette et al 110,111 showed that in rabbits with pacing induced heart failure, statin therapy with simvastatin normalizes sympathetic outflow and cardiovascular reflex regulation and showed a beneficial dose-dependent effect on baroreceptor sensitivity. The underlying mechanism for the beneficial effects of statin therapy in modulating the autonomic nervous system was further elucidated by recording renal sympathetic nerve activity and studying the effect of statins on angiotensin II type I gene expression and nicotinamide adenine dinucleotide phospate (NADPH) oxidase activity (a downstream protein activity by angiotensin II receptor activation) in the rostral ventrolateral medulla of rats.…”
Section: Medical Therapies Modulating Cardiac Autonomicsmentioning
confidence: 99%